2009
DOI: 10.1080/10790268.2009.11754465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Disorders of Carbohydrate and Lipid Metabolism in Adults With Traumatic Spinal Cord Injury: Systematic Review of the Evidence

Abstract: Background/Objective: Carbohydrate and lipid metabolism disorders may affect adults with spinal cord injuries (SCIs) differently than able-bodied individuals because of reduced physical activity in the SCI population. The objective of this study was to conduct a systematic review to determine the effectiveness of exercise to improve carbohydrate and lipid metabolism disorders in adults with chronic SCI. Methods: Studies were identified in MEDLINE (1996MEDLINE ( -2008, Cochrane Library, bibliographies of identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
(152 reference statements)
0
24
0
Order By: Relevance
“…It is well known that deconditioning reduces the antioxidant capacity and increases oxidative stress in patients with chronic respiratory insufficiency [41] as well as in animal models of hindlimb suspension [42]. However, deconditioning can be ruled out in our study because (i) it induces carbohydrate and lipid disorders [43] that were not observed during routine biochemical Values are the mean ± SEM. *P < 0.05; **P < 0.01; ***P < 0.001, significant difference from control subjects.…”
Section: Methodological Considerationsmentioning
confidence: 74%
“…It is well known that deconditioning reduces the antioxidant capacity and increases oxidative stress in patients with chronic respiratory insufficiency [41] as well as in animal models of hindlimb suspension [42]. However, deconditioning can be ruled out in our study because (i) it induces carbohydrate and lipid disorders [43] that were not observed during routine biochemical Values are the mean ± SEM. *P < 0.05; **P < 0.01; ***P < 0.001, significant difference from control subjects.…”
Section: Methodological Considerationsmentioning
confidence: 74%
“…4 The same study reported improvement in both plasma glucose and insulin; however, it did not show any improvement in plasma cholesterol levels or triglycerides as well as reduction in high-density lipoprotein-C. 4 A review summarizing evidence from 22 studies contended that there is insufficient support to the hypothesis that exercise could improve carbohydrate and lipid disorders among adults with SCI. 6 The factors that are responsible for these controversial results need to be well studied to ensure successful controlled interventions. SCI is a complex medical condition where deterioration in body composition and metabolic profile is defined by the nature or level of injury, completeness of injury, time since injury, and age of the participants.…”
Section: 45mentioning
confidence: 99%
“…29 A recent systematic review concluded that there is insufficient evidence to determine whether exercise improves carbohydrate and lipid metabolism disorders among adults with SCI. 30 Kehn and Kroll 31 highlighted the many barriers to exercise by people with SCI, including: a perceived low return on physical investment, lack of accessible facilities, unaffordable equipment, no personal assistance, and fear of injury. There are examples of local initiatives that encourage regular exercise after SCI, for example, Mac Wheelers program at McMaster University and the Steadward Centre at the University of Alberta, which offer low-cost, supervised exercise facilities in a central location.…”
Section: Activity and Fitnessmentioning
confidence: 99%